Emphysematous lungs do not affect visibility of virtual-assisted lung mapping. (February 2016) - Yamanashi, Keiji; Sato, Masaaki; Marumo, Satoshi; Fukui, Takamasa; Sumitomo, Ryota; Shoji, Tsuyoshi; Otake, Yosuke; Katayama, Toshiro; Huang, Cheng-Long
Background: It has recently been suggested that virtual-assisted lung mapping may enable safer and more reliable intraoperative navigation compared to conventional preoperative lung marking strategies. This study aimed to examine the relationship between emphysematous lungs and the intraoperative visibility of virtual-assisted lung mapping markings. Methods: We retrospectively analyzed the data of 21 patients who underwent virtual-assisted lung mapping followed by lung resection between October 2013 and May 2015. The visibility of the intraoperative lung markings was graded. The degree of pulmonary emphysema was assessed by the percentage of low attenuation area on computed tomography. We elucidated the associations between the marking grade and other factors such as patient age or sex, pulmonary lobe mapped, marking operator, Brinkman index, and percentage of low attenuation area of the pulmonary lobe. Results: In Spearman rank correlation analysis, there was no correlation between the Brinkman index and the percentage of low attenuation area ( n  = 26, r  = −0.016, p  = 0.937). In stepwise multivariate regression analysis, the marking grade correlated with the marking operator ( p  < 0.001) and the Brinkman index ( p  = 0.008), but not with patient age or sex, the pulmonary lobe mapped, or degree of pulmonary emphysema. Conclusion: The skill of the marking operator and the patient's smoking history had significant effects on the intraoperative visibility of markings made by virtual-assisted lung mapping, whereas emphysematous lungs did not affect the intraoperative visibility of lung markings.